National Table on Displacement: Political violence, peasant communities and rural institutions in the central-southern highlands - Monge, Carlos (2001)
This article is the result of the collective reflection carried out within the framework of the project "Strengthening Democratic Institutions in Zones Affected by Violence", implemented by the National Roundtable on Displacement. The objective of the aforementioned project has been to define, in a collective and participatory manner, intervention strategies in the areas affected by violence that tend to strengthen democratic institutions as a central axis of concern.